A history of Egypt from the end of the Neolithic Period to the death of Cleopatra VII B.C. 30. Egypt under Rameses the Great / Volume 5, (2013) - Sir, Budge, E. A. Wallis (Ernest Alfred Wallis), 1857-1934
No abstract available